THE INFLUENCE OF CORPORATE CULTURE AND ITS ENVIRONMENT TO WARD THE ENTREPRENEURSHIP ORIENTATION AND MARKETING STRATEGY AND ITS IMPACT TO THE PERFORMANCE OF A COMPANY AT CIPUTRA GROUP - siswoyo, siswoyo (Archives of Business Research, 2020)
The growth of the property industry makes one of the companies engaged in the property sector such as Ciputra Group have many competitors that are starting to emerge. In this case, the strategy is very important for Ciputra Group, considering that sales in the first semester of 2015 decreased by 90 percent. This makes PT Ciputra Development Tbk implement a market expansion strategy especially the middle to lower segments. The Company also needs to concern the strategic marketing management practices to ensure that the strategies are suitable to be established within the organization. The purpose of this study is to prove and analyze the influence of the corporate culture and its environment toward the company performance by mediating entrepreneurial agreements and marketing strategies at Ciputra Group. This research based on the time of the observation, named crossectional study, and the type of the usefulness named explanatory study. The research was conducted at Ciputra Group Company in August till September 2018. The sample population was 148 subsidiary companies from PT Ciputra Development Tbk. The data analysis technique used Structural Equation Modeling (SEM) with AMOS V24 software. The result of the analysis provide a conclusion that the company’s environment has a significant effect on entrepreneurship orientation and company’s performance, but it has no effect on marketing strategy. Corporate culture only has a significant effect on entrepreneurship orientation and marketing strategy, while there is no directly significant effect toward the company‘s performance. Furthermore, entrepreneurship orientation and marketing strategy have a significant effect to the company’s performance.